Del absurdo a la esperanza: Vacío existencial y sed de misterio en el hombre de hoy - Maurial, Iván (2000)
According to Logoterapy of V. Frankl, the human being is guided beyond itself, in search of a sense for his life (Will of Sense). When this primary orientation is frustrated, is experience the Existential Hole that unchains in neurotic aspiration to the power (Adler) and to the pleasure (Freud). The authors expose on the boredom like main feeling of the Existential Hole with examples of happening local and worldwide. Likewise, it presents the hurry like escape and the fascination for the absurdity as alliance with their existential frustration.